Damage to concrete bridges due to reinforcement corrosion: Part I. Site investigations - Kamaitis, Zenonas (Transport, 2002)
Corrosion of reinforcement initiated by concrete carbonation and chloride contamination is the most common type of deterioration of concrete bridges. Based on the author’s experience a number of cases is reported in which the corrosion of ordinary and prestressed reinforcement as well as the causes and consequences of deterioration observed are presented. Investigations have shown that the main reasons are: insufficient concrete cover, poor quality of concrete, and ingress of aggressive salts. The carbonation depth must be related to the histogram ofrebar cover depths and the probability of their coincidence can be predicted. The monitoring of tendon conditions in prestressed concrete precast post-tensioned segmental bridge decks shows that the voids and the water are often present in the ducts leading to the local rusting of tendons. The wires used in tendons are liable to fail in tension that was observed in some prestressed concrete bridges. Unfortunately, no reliable procedures of determining the condition of prestressing steel in existing structures are available. First Published Online: 19 Dec 2011